NILAI ESTETIS BATIK SITUBONDO HASIL TRANSFORMASI LUKISAN VONI WIJAYANTI - Wijayanti, Voni; -, Hardiman; Sura Ardana, I Gusti Ngurah (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2015)
This study was aimed at describing the aesthetic value of Batik Situbondo that was transformed from Voni Wijayantiâ€™s painting. This research was action research. Subjects were craftsmen â€œSaung Batik Puspa Bahariâ€ in the village of Asembagus, Kec. Asembagus, Situbondo; some of them are professional and academician of art. Data collection techniques used in this research are observation, interviews, discussions (FGD), documentation, and literature. The results of this research showed the aesthetic value in Batik Situbondo painting transformed from Voni Wijayanti consisting of design principles and the principles of design.Keywords: transformation, Voni Wijayanti painting, batik Situbondo, aesthetic value